Hubungan Pengetahuan Dan Sikap Masyarakat Dalam Kesiapsiagaan Bencana Banjir Bandang Di RW 6 Kelurahan Jodipan Kota Malang - Pandi, Lastriani Astuti; Saktiawan, Yusup; Sari, Devita (POLTEKKES KEMENKES MANADO, 2022)
Flood disaster preparedness is a series of activities undertaken in anticipation of disasters by doing organized plans in appropriate and efficient steps. Good knowledge and attitude will be one of the most important factors on the community and they have relationship in the preparedness of flash flood as the disaster. The purpose of this study is to determine the relation between knowledge and public attitude on flash flood disaster preparedness. This research method used a quantitative design with a cross-sectional approach. The sample of this research was 72 respondents. Determination of the sample using probability sampling technique by proportioning the number of samples using proportional stratified random sampling technique. Tha Statistical test used was chi-square test. Based on the study found the results that there was a relation between knowledge on flood disaster preparedness, p=0.043. Attitude in preparedness is p=0.048. Facilities and infrastructure in flood disaster preparedness is p = 0.000. The most risky factors for flash flood disaster preparedness are knowledge and attitudes with a significant value of knowledge p = 0.043 and attitude p = 0.048. So, it can be concluded that there is a relation between knowledge and public attitudes on flash flood disaster preparedness